2013
DOI: 10.3390/md11125036
|View full text |Cite
|
Sign up to set email alerts
|

Screening Mangrove Endophytic Fungi for Antimalarial Natural Products

Abstract: We conducted a screening campaign to investigate fungi as a source for new antimalarial compounds. A subset of our fungal collection comprising Chinese mangrove endophytes provided over 5000 lipophilic extracts. We developed an accelerated discovery program based on small-scale cultivation for crude extract screening and a high-throughput malaria assay. Criteria for hits were developed and high priority hits were subjected to scale-up cultivation. Extracts from large scale cultivation were fractionated and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 25 publications
1
33
0
2
Order By: Relevance
“…However, these compounds have inhibitory activities against four tumor cell lines and α-glucosidase (Wang et al 2017;Lee et al 2017). Calcul et al (2013) reported the antimalarial compounds produced by endophytic fungi from mangroves. Previously, Ravikumar et al (2011) also reported the antimalarial activity and the chemical content of mangrove plants is alkaloids, triterpenes, flavonoids, tannins, catechins, anthraquinones, phenols, sugars, and proteins.…”
Section: Discussionmentioning
confidence: 99%
“…However, these compounds have inhibitory activities against four tumor cell lines and α-glucosidase (Wang et al 2017;Lee et al 2017). Calcul et al (2013) reported the antimalarial compounds produced by endophytic fungi from mangroves. Previously, Ravikumar et al (2011) also reported the antimalarial activity and the chemical content of mangrove plants is alkaloids, triterpenes, flavonoids, tannins, catechins, anthraquinones, phenols, sugars, and proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Dicerandrol D 433 exhibited potent activity against P. falciparum with relatively low toxicity to A549 cells. 373 Endophytic Fusarium proliferatum (mangrove Bruguiera sexangula, Hainan Is., China) produced the tricyclic sesterterpenes fusaprolin A 437 and B 438 and the 2H-pyran-2-one derivatives prolipyrone A-C 439-441. Fusaprolins A and B had modest activity against brine shrimp.…”
Section: Fungi From Mangrovesmentioning
confidence: 99%
“…Beau and colleagues reported that epigenetic tailoring of the marine fungus Leucostoma persoonii enhanced production of the known polyketide cytosporone E ( 67 ), which inhibited P. falciparum with significant selectivity [74]. Calcul and colleagues reported a massive screening of Chinese mangrove endophytic fungi and discovered several new compounds, including a novel dimeric tetrahydroxanthone polyketide dicerandrol D ( 68 ), which was potent against “a robust and validated” drug-sensitive P. falciparum strain 3D7 [75]. Ilias and colleagues reported a novel pentacyclic ingamine alkaloid dihydroingenamine D ( 69 ), isolated from a sponge Petrosid Ng5 sp.5, which showed strong antiplasmodial activity against P. falciparum D6 and W2 strains [76].…”
Section: Marine Compounds With Antibacterial Antifungal Antiprotmentioning
confidence: 99%